Recent Freshening, Warming, and Contraction of the Antarctic Bottom Water in the Indian Sector of the Southern Ocean - Anilkumar, N; Jena, Babula; George, Jenson V.; P, Sabu; S, Kshitija; Ravichandran, M (Frontiers in Marine Science, 2021)
High saline and cold Antarctic Bottom Water (AABW) forms around the continental margin of Antarctica that ventilates into the global ocean. To study the recent changes in AABW, we have analyzed the in situ observations collected from Indian Ocean expeditions to the Southern Ocean during 2010, 2011, 2017, 2018, and 2020. A comprehensive analysis of these observations indicated recent freshening, warming, and contraction in the layer thickness of the AABW. Even though the AABW depicted inter-annual variability, it changed to moderately fresher and lighter water mass at the end of the recent decade. The characteristics of AABW exhibited a contraction in its layer thickness (∼50–120 m) during recent years. The water mass showed its freshening (∼0.002) and warming (∼0.04°C) tendency from 2018 to 2020. The recent warming (∼0.3°C) of Circumpolar Deep Water (CDW) near the Prydz Bay suggests enhanced melting of ice shelves. It is hypothesized that the combined influences of onshore intrusion of warm CDW, upper ocean warming, sea ice decline, wind forcing, polynya, and calving events possibly caused the freshening and reduction in the thickness of AABW. The continued changes in the ocean-atmospheric environmental conditions and the subsequent changes in the bottom water characteristics likely influence the global climate, overturning circulation, and the biogeochemical cycle.